The Role of Education in Sustainable Development(Between Theory and Practice) - Dr. Ahlam Hameed Nima Al-Janabi (Journal of College of Education, 2025)
The article aims to demonstrate the role of education in achieving sustainable development by identifying the economics of education and sustainable development, which has become an urgent necessity for education to keep pace with modern requirements. It is a vision that aims to achieve positive change in the educational process and ensure its continuity to meet the basic needs of future generations
Keywords: Education, Social Development, Sustainable Society.